An alternative proposal for the implementation of the folded line equivalent - Timaná, Luis; Colqui, Jaimis S.L. [UNESP]; Kurokawa, Sérgio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This article presents an alternative transmission line model, using the formulation of the Folded Line Equivalent (FLE). The model is based on Norton equivalents derived from the FLE short-circuit and open-circuit admittance matrices and an interface, which is represented by ideal transformers, as a means of transformation between the phase domain of the line and the FLE short-circuit and open-circuit conditions. The alternative model is used to represent a short-length transmission line. The simulation results are compared with the JMarti and Ulm models from the ATP-EMTP and PSCAD/EMTDC programs, respectively. These results show that the alternative model can represent an advantage for short lines, since it is possible to use integration time steps longer than the transmission line propagation delay without having a significant negative effect on the transient responses.
Keywords: Folded line equivalent; Norton equivalent; Passivity; Transmission line; Vector fitting